Embeddedness analysis of a native Chinese NGO participating in international plastic treaty negotiations from the perspective of network institutionalism - Zhao, Yan; Gao, Guangyue; Wang, Huo (Frontiers in Marine Science, 2025)
In the global governance of marine plastic pollution, the “negotiation-driven governance model” of accelerating negotiations is used in order to issue plastics treaties to deal with the problem of plastic pollution including marine plastic pollution while little empirical evidence exists concerning the participation process and strategy of native Chinese NGOs in plastics treaty negotiations. To illustrate the embeddedness strategy that native Chinese NGOs used to attract resources from social individuals and strive for a voice in the “Intergovernmental Negotiation Conference (INC), this research utilized observation method and is grounded in a series of interviews to collect the first-hand data, utilizing the Nvivo12 software with the three-phase bottom-up coding approach to analysis these interview transcripts. After a single qualitative case study under a normative bridging framework which is developed by “embeddedness” combined with network institutionalism theory, this research finds the complex and nuanced development of a native Chinese NGO in plastic treaty negotiations, it connects with social individuals by nomination under the dual registration system in China, and embeds in international affairs through side events and non-official events with the observer status. This research empirically contributes to existing network institutionalism theories through the development of a NGO normative bridging framework to illustrate the relationship between native Chinese NGOs, individuals, and international negotiations in world political and international relationship issues.